Features of the dynamics of seismic activity in models of the FitzHugh-Nagumo type - V. B. Spirtus (Геофизический журнал, 2011)
This paper considers the models of the Fitzhugh-Nagumo type, used to description of seismic activation. The examples of quasi-periodic dynamics and existence of homoclinic trajectories proper to the travelling impulses are resulted. For a twomode nondiffusion model the dynamic system of equations, linking amplitudes of the first and third fashions, is got. As physical explanation of the phenomenon of seismic quiescence competition of fashions is offered.